Investigating risk factors behind piglet facial and sow teat lesions through a literature review and a survey on teeth reduction - Chou, Jen-Yun; Marchant, Jeremy N.; Nalon, Elena; Huynh, Thuy T. T.; van de Weerd, Heleen A.; Boyle, Laura A.; Ison, Sarah H. (Frontiers in Veterinary Science, 2022)
Piglet facial and sow teat lesions are the main reported reasons why pig producers routinely practise teeth resection. This is a painful procedure performed on piglets, where their needle teeth are clipped or ground to resect the pointed tip. The practice raises welfare concerns. In contrast to other procedures, such as tail docking, we know little about the risk factors for these two types of lesions. We employed two methods to answer these questions: 1) reviewing the literature to identify potential risk factors, and 2) surveying pig production stakeholders worldwide to identify the occurrence of these lesions and the strategies used in practice that enable pig producers to manage or prevent these lesions while avoiding teeth resection. For the literature review, we used Google Scholar to include peer-reviewed publications and grey literature. We distributed the survey using convenience sampling and documented information on the current situation regarding teeth resection, including the methods, frequencies, and reasons for resecting piglets’ teeth, the occurrence of piglet facial and sow teat lesions, and measures used to prevent and control these lesions. The literature review identified six major risk factors for both lesions, including the presence or absence of teeth resection, housing system, litter size, piglet management, environmental enrichment, milk production and other piglet management practices. However, most studies focused on the effects of the first two factors with very few studies investigating the other risk factors. There were 75 responses to the survey from 17 countries. The survey showed that half of the respondents practised teeth resection with many recognising that facial and teat lesions are the main reasons behind this practice. However, many producers used other interventions rather than teeth resection to prevent these lesions. These interventions focused on improving milk production of the sow, managing large litters, and providing environmental enrichment. More research is needed to validate these interventions and more science-based advice is needed to bridge the gap between research and practice to help more producers further understand the cause of piglet facial and sow teat lesions to transition towards the cessation of routine teeth resection.